EMBEDDING SUSTAINABILITY INTO DATA PRACTICES FOR DIGITAL TRANSFORMATION: A SYSTEMATIC REVIEW - Viriyasitavat, Wattana; Pattanapanyasat, Ra-pee; Hoonsopon, Danupol; Rhuwadhana, Phoranee; Charoenruk, Nuttirudee; Pungpapong, Vitara (Journal of Posthumanism, 2025)
This study advocates a “Sustainable-by-Design” approach that embeds sustainability throughout the data lifecycle—from collection to disposal—within digital transformation (DT). Based on a systematic literature review of 55 peer-reviewed articles (2006–March 2025), and guided by Dynamic Capabilities Theory, RBV/NRBV, and Institutional Theory, the paper identifies seven key enablers: Sustainable Data Analytics and AI, Strategy Alignment, Organizational Capabilities, Infrastructure, ESG Governance, Data Design, and Institutional Pressures. These are synthesized into a three-stage maturity model—Foundational, Integrated, and Transformative. Findings highlight a focus on internal capabilities while institutional forces remain underexplored. The study contributes a multi-theoretical framework and offers practical guidance for embedding ESG principles into data governance, promoting responsible and regenerative DT.